Pengaruh Penerapan Model Pembelajaran Problem Based Learning Berbasis Media Komik terhadap Hasil Belajar Siswa dalam Mata Pelajaran PPKn Kelas VIII di SMP Negeri 2 Lingsar - Laelatul Fajri; Edy Herianto; Sawaludin Sawaludin (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
This study aims to determine the influence of the application of the comic-based Problem Based Learning learning model on learning outcomes. The approach used is quantitative with a type of Nonequivalent Control. The research sample consisted of two classes, namely class VIII (6) and VIII (8) with Purposive Sampling techniques. The instrument used is a multiple choice test. Test The analysis requirements used for the normality test are the Liliefors Test and the homogeneity test using the variance test. For hypothesis testing using the sign test test. The results of the study obtained that P = 0.05 > the price of P(2) = 0.0002, then Ho was rejected, meaning that there was a significant influence in the influence of the application of the comic-based Problem Based Learning learning model on student learning outcomes in the subject of PPKn class VIII SMPN 2 Lingsar. The application of the comic-based Problem Based Learning learning model proves that there is an increase in student learning outcomes in ppkn subjects and in accordance with their learning objectives.